2016
DOI: 10.18632/oncotarget.9358
|View full text |Cite
|
Sign up to set email alerts
|

NPR-C gene polymorphism is associated with increased susceptibility to coronary artery disease in Chinese Han population: a multicenter study

Abstract: To find a new locus that confers significant susceptibility to CAD in Chinese Han population, a genome-wide association study in 200 “extreme individuals” from a Shandong cohort and a pathway-based candidate gene study from a Shanghai cohort (293 CAD/293 controls) were simultaneously performed. Amongst them, 13 SNPs associated with CAD were selected to conduct validation and replication studies in additional 3363 CAD patients and 3148 controls. A novel locus rs700926 in natriuretic peptide receptor C (NPR-C) w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
12
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 27 publications
1
12
0
Order By: Relevance
“…NPR3 (also known as NPR-C) encodes one of three receptors of natriuretic peptide which are small peptides responsible for regulating blood volume and pressure [29]. Several variations of NPR3 have been previously shown to be related to essential hypertension and coronary artery disease [30,31]. Follow-up functional studies are needed to investigate the mechanisms by which these genes contribute to the development of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…NPR3 (also known as NPR-C) encodes one of three receptors of natriuretic peptide which are small peptides responsible for regulating blood volume and pressure [29]. Several variations of NPR3 have been previously shown to be related to essential hypertension and coronary artery disease [30,31]. Follow-up functional studies are needed to investigate the mechanisms by which these genes contribute to the development of cardiomyopathy.…”
Section: Discussionmentioning
confidence: 99%
“…NPR-C signal transduction may also play an important role in the pathogenesis of atherosclerosis [17]. Recently, several novel single nucleotide polymorphisms (SNPs) of NPR-C were identified to be associated with atherosclerotic cardiovascular disease (ASCVD) in Han Chinese population [40]. Interestingly, multivariate logistical regression analysis demonstrated that the association between these SNPs and ASCVD remained significant even after adjustment for all the conventional risk factors of ASCVD including hypertension [40].…”
Section: Consequences Of Npr3 Mutation And/or Alterations In Npr-cmentioning
confidence: 99%
“…Recently, several novel single nucleotide polymorphisms (SNPs) of NPR-C were identified to be associated with atherosclerotic cardiovascular disease (ASCVD) in Han Chinese population [40]. Interestingly, multivariate logistical regression analysis demonstrated that the association between these SNPs and ASCVD remained significant even after adjustment for all the conventional risk factors of ASCVD including hypertension [40]. Although the underlying molecular mechanisms of the association between NPR-C gene polymorphism and ASCVD are unclear, some studies have shown that percutaneous coronary intervention-induced injury to neointima may lead to an increase in NPR-C expression in neointimal smooth muscle cells [17].…”
Section: Consequences Of Npr3 Mutation And/or Alterations In Npr-cmentioning
confidence: 99%
“…[ 3 ] Using genome-wide association study (GWAS), more than 57 loci have been identified that contribute to risk of CAD or its major complication, myocardial infarction (MI). [ 4 9 ] Many of these loci are associated with known risks factors for CAD, such as low-density lipoprotein cholesterol (LDL-C) levels and blood pressure, which are the primary treatment targets for patients with CAD. However, the associations between these variants and clinical outcome of CAD were evaluated in comparatively few studies.…”
Section: Introductionmentioning
confidence: 99%